2017
DOI: 10.1016/j.celrep.2017.08.089
|View full text |Cite
|
Sign up to set email alerts
|

Tumor-Derived Mesenchymal Stem Cells Use Distinct Mechanisms to Block the Activity of Natural Killer Cell Subsets

Abstract: Mesenchymal stem cells (MSCs) display pleiotropic functions, which include secretion of soluble factors with immunosuppressive activity implicated in cancer progression. We compared the immunomodulatory effects on natural killer (NK) cells of paired intratumor (T)- and adjacent non-tumor tissue (N)-derived MSCs from patients with squamous cell lung carcinoma (SCC). We observed that T-MSCs were more strongly immunosuppressive than N-MSCs and affected both NK function and phenotype, as defined by CD56 expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
75
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(78 citation statements)
references
References 59 publications
2
75
0
1
Order By: Relevance
“…80 In addition, the direct cross-talk between NK cells and intratumor stromal cells pathologically contributes to alter NK cell phenotype in lung carcinoma. 81 Similar results were obtained also in invasive breast cancer where NK cells show an increased expression of NKG2A and a decreased expression of the aNKRs NKp30, NKG2D, DNAM-1, and CD16. 82 In this context, the increased expression of HLA-E on tumor cells is associated with a higher incidence of relapse in breast cancer 83 and with a worst prognosis in colorectal adenocarcinoma.…”
Section: Nk Cell Immune-reconstitution and Nkg2a In Hsctsupporting
confidence: 76%
See 1 more Smart Citation
“…80 In addition, the direct cross-talk between NK cells and intratumor stromal cells pathologically contributes to alter NK cell phenotype in lung carcinoma. 81 Similar results were obtained also in invasive breast cancer where NK cells show an increased expression of NKG2A and a decreased expression of the aNKRs NKp30, NKG2D, DNAM-1, and CD16. 82 In this context, the increased expression of HLA-E on tumor cells is associated with a higher incidence of relapse in breast cancer 83 and with a worst prognosis in colorectal adenocarcinoma.…”
Section: Nk Cell Immune-reconstitution and Nkg2a In Hsctsupporting
confidence: 76%
“…Moreover, the up‐regulation of NKG2A on NK cells in patients with lung cancer is a predictive factor of tumor metastatization . In addition, the direct cross‐talk between NK cells and intratumor stromal cells pathologically contributes to alter NK cell phenotype in lung carcinoma . Similar results were obtained also in invasive breast cancer where NK cells show an increased expression of NKG2A and a decreased expression of the aNKRs NKp30, NKG2D, DNAM‐1, and CD16 .…”
Section: Nkg2a In Tumorssupporting
confidence: 65%
“…Consistent with these observations, Vasandan et al elucidated a metabolic alteration of M1 proinflammatory (antitumor subtype) macrophages toward antiinflammatory M2 (protumor subtype) macrophages in a mechanism involving production of PGE2 (31). In addition, Galland and others have also highlighted that tumor-derived MSCs block NK cell activity in a direct interaction through production of PGE2 (16,32). Although we found that monocytes become suppressor cells when exposed to MDS-MSCs, we did not observe a significant increase in PGE2 in our transcriptome analysis.…”
Section: Discussionmentioning
confidence: 84%
“…MSC-EVs also effectively inhibit antigen-presenting-cell activation and suppress Th1 and Th17 in type 1 diabetes and uveoretinitis(Shigemoto-Kuroda et al, 2017).7 | INTERACTION BETWEEN MSCS AND MSC-EVS AND INNATE IMMUNE CELLSBesides all aforementioned details about T and B cells, MSCs have proven effects on NK cells. HLA-G secreted by MSCs mitigates degranulation activities of NK cells therefore the cell lyses would be blocked(Galland et al, 2017). NK cell proliferation and function were indicated to be affected by IDO, TGFβ, and PGE2, which are secreted by MSCs.…”
mentioning
confidence: 99%